DRAMA PERAMPASAN YANG DIBAYANGKAN: ARTIKULASI IDENTITAS DAN KEPEMILIKAN PRIMORDIAL KELOMPOK IDENTITAS ASLI PASCA ORDE BARU - Riyanto, Geger (Masyarakat Indonesia, 2018)
The post-New Order period witnessed the resurgence of the discourse of indigenous identity in various lines of social life in Indonesia. As authenticity often underlies the claims, struggles, or protection of resource ownership in the diverse groups, the notion that the discourse of identity is recreated and manipulated in order to emphasize control over resources becomes commonplace. However, this article would like to show that moral intuition and supposition also have a meaningful contribution in enabling indigenous identity maneuvers. Regardless of the chance of securing resources, undeniably encouraged the parties to identify themselves as indigenous, the narratives of indigenous people’s rights are usurped by outsiders that constantly accompanying the rhetoric of the original identity group. By personalizing and simplifying impersonal entities such as corporations, states, immigrants become fictional human beings who violate their moral obligations by depriving what the original group actually possesses. As imagined as fictional human beings, primordial possession narrative has an evocative power that unifies members and invitee’s response of other parties. Furthermore, it also serves as a foothold of structures that bind and organize the actions of the human beings that involved. The rules, institutions, and maneuvers of actors must be realized to comply with their discursive logic.